2016
DOI: 10.2147/ndt.s123239
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a mindfulness-based intervention program for people with schizophrenia: 6-month follow-up

Abstract: Mindfulness-based interventions have been increasingly evidenced to be effective in different mental illnesses but limited in schizophrenia. This single-blind, multisite randomized controlled trial tested the effects of a mindfulness-based psychoeducation group program (MPGP in addition to usual care) versus a conventional psychoeducation group program (CPGP) versus treatment-as-usual (TAU) alone, in schizophrenia spectrum disorders over a 6-month follow-up. In each of the two study sites (outpatient clinics),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
0
44
0
2
Order By: Relevance
“…Drake et al 164 found that cognitive therapy which followed cognitive remediation was linked to greater improvements in clinical insight in psychosis. Motivational interviewing 165,166 and mindfulness based interventions [167][168][169] have also been linked to improved insight relative to treatment as usual.…”
Section: Psychological Interventions Which Can Affect Insightmentioning
confidence: 99%
“…Drake et al 164 found that cognitive therapy which followed cognitive remediation was linked to greater improvements in clinical insight in psychosis. Motivational interviewing 165,166 and mindfulness based interventions [167][168][169] have also been linked to improved insight relative to treatment as usual.…”
Section: Psychological Interventions Which Can Affect Insightmentioning
confidence: 99%
“…Additional studies of MBIs have revealed an improvement in social functioning (68) and self-esteem (69). Furthermore, MBIs proved to reduce rehospitalization rates, up to one-fourth compared to participants that received treatment as usual (TAU) (68,(70)(71)(72)(73). A study also reported shorter in-patient treatment durations from an average of 18.2 days with TAU to 11.8 days per year in the group with MBIs at an 18-month follow up (72).…”
Section: Introductionmentioning
confidence: 99%
“…While several trials have supported the effects of mindfulnessbased interventions for psychotic patients (14)(15)(16)(17), the mechanism that explains how mindfulness skills benefit psychotic patients has been underexplored. There is evidence that mindfulness-based interventions can improve mental health and well-being through reducing rumination and worry in adults with depressive symptoms, anxiety disorders and cancer (18).…”
Section: Introductionmentioning
confidence: 99%